PEMODELAN MATEMATIK ALIRAN TITIK GENANGAN DAN PEMINDAHAN HABA TERHADAP PERMUKAAN MEREGANG/MENGECUT - Nor Ain Azeany Mohd Nasir (Thesis, 2020)
The five problems of stagnation point boundary layer flow and heat transfer over stretching/shrinking surfaces considered in this study are : (i) Stagnation point flow over permeable quadratically streching/shrinking surfaces (ii) stagnation point flow Magnetohydrodynamic (MHD) nanofluid past a stretching/shrinking surfaces with convective boundary condition and radiation effects (iii) MHD stagnation point flow over stretching/shrinking surfaces with induced magnetic field effect ; (iv) stagnation point flow over strecthing/shrinking Riga plates with slip velocity and radiation effects (v) MHD stagnation point flow past stretching/shrinking surfaces with heat sink and radiation effects. All mathematical model being studied.